La comprensión lectora en la educación primaria y las estrategias metodológicas para su enseñanza - Ramírez Paredes, Fredith (2013)
The basic purpose that guided this monographic work of compilation was the systematize the most relevant aspects of the theory of reading comprehension and propose methodological strategies most appropriate for their application in the process of teaching and learning at the primary level, in the light of the experiences of researchers who have been addressing this pressing problem that affects large sectors of students in the country. In this perspective, our attention is focused in describe them concepts more general that characterized to the reading as praxis of the understanding and its intimate relationship with them habits that must be inculcated from the school and the home. In this sense, highlights the fundamental role played by the family in the formation of the healthy habit of reading. On the other hand, stands out that reading is a process of interaction between the reader and the text, process by which the reader establishes an intimate communication with the gr...